Mandibular teeth as predictors in forensic age estimation: A cone-beam computed tomography-based pulp volume regression study - Akshay Rathore; Nidhi Puri; Balwinder Singh; Kirandeep Kaur; Bikramjeet Singh; Shivangi Singh (Wolters Kluwer Medknow Publications, 2023)
Background: Age estimation is integral to science of forensic odontology and plays an important role in human identification. Pulp volume estimation using cone-beam computed tomography (CBCT) to derive age can be very useful as it is noninvasive and can be applied on individuals of all ages. Aims and Objectives: The study aimed to estimate the chronological age-based pulp and tooth volume (PTV) ratios in adults from Uttar Pradesh, India, using CBCT and voxel counting dental software. Materials and Methods: Thirty-six CBCT scans were allocated into three Groups, I, II, and III (12 in each group) randomly to study the pulp volume of lateral incisor, canine, and first premolar, respectively. PTV was calculated by image segmentation method using Xelis Dental software. A correlation between chronological age with PTV was established using derived regression equations. Statistical Analysis: All the data were subjected to statistical analysis using Statistical Package for Social Sciences version 16.0. Results: Estimated age and standard error were determined. Standard errors of estimates were 11.24 years (LI), 7.78 years (C), 9.89 years (PM) group, lowest being for canines. The estimated age was compared with the chronological age. The difference between the chronological age and the estimated age by the derived equation for the present study was statistically nonsignificant (P = 1.00). Conclusions: The results of the study show the feasibility of calculation of PTV ratios on CBCT to estimate the age for the set population with canine as the best predictor of age for the present study population.